Induction of amplified synthesis and secretion of IgM by fusion of murine 'b lymphoma with myeloma cells. - Laskov, R (1979)
Murine B lymphoma cultured cell lines bearing membrane IgM and lacking the ability to secrete measurable amounts of IgM were fused with drug-resistant cell lines derived from the IgG2b-producing MPC-11 myeloma. Many of the hybrid clones synthesized and secreted large amounts of IgM, as judged by radial and double immunodiffusion in agar of culture supernatants and by polyacrylamide gel electrophoresis of biosynthetically labeled IgM. When fused with an IgG2b-producing myeloma, many of the hybrids also produced IgG2b, indicating that there was no suppression of the parental IgG synthesis in the hybrids. The amount of IgM or IgG2b secreted by the hybrids was higher than that secreted by myeloma cell lines. The synthesis of the gamma2b heavy chain of the MPC-11 myeloma was not reexpressed by fusion of a gamma2b nonproducer myeloma cell variant with B lymphoma. No other classes of Ig heavy chains, besides the gamma2b and the mu chains, were found to be secreted by any of more than 100 B lymphoma--myeloma hybrids examined. The results of the present work suggest that myeloma cells may fuse not only with normal plasma cells but also with less-mature normal B lymphocytes and that this fusion "induces" the maturation of B lymphocytes into IgM-secreting cells.